How long does it take to translate research findings into routine healthcare practice? : the case of biological drugs for rheumatoid arthritis in Brazil - Lupatini, Evandro de Oliveira (2022)
Background: The literature reports long time lags between the several processes involved in the translation of drug research and development into clinical application. To expedite these processes, translational research has emerged as a process that can be applied to reduce the lag between scientific discoveries and their practical application. Thus, the objective of this study was to estimate the time lag in translational research of biological drugs for the treatment of rheumatoid arthritis included in the Brazilian Unified Health System [Sistema Único de Saúde (SUS)]. Methods: A descriptive retrospective study was conducted based on secondary data loaded by SUS users in public sources and systems to estimate the time lag between the publication of phase I clinical trial results to drug use in clinical settings. The dates of translational research activities were identified from markers and steps. Structured searches were conducted in the literature and reports from the National Commission for the Incorporation of Technologies in the SUS (Conitec) as well as from health authorities, and analyzed. Results: Between 2012 and 2019, SUS included five biological agents for the treatment of rheumatoid arthritis. The mean time lag from clinical development to use of these agents was 11.13 years (range, 8.57 to 12.90 years). The mean time lag for the stages of translational research were 5.30 (T1—basic research to clinical research), 5.08 (T2—clinical research to research synthesis), and 0.75 (T3—research synthesis to evidence-based practice) years. A shorter time lag was observed in the Brazilian case when it was possible to compare with other studies. Conclusions: The estimated time lag of biological drugs used in the treatment of rheumatoid arthritis was determined based on the translational research steps model adapted to the Brazilian context. Brazil has instituted legal frameworks that set deadlines for sanitary registration, health technology assessment (HTA), and the availability of drugs in the SUS, thus, allowing for a reduced stage T2 time lag. Nevertheless, improvements are still required in stages T1 and T2, especially in publishing the results of clinical trials.